2019
DOI: 10.3390/ijerph16244984
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sugar-Sweetened Beverage Consumption as Meal Substitutes, Workload, and Obesity in Nurses: A Cross-Sectional Study

Abstract: Background: High occupational stress has been associated with altered eating behaviors and obesity. Occupational stress is reported to be high in Asian countries. Furthermore, many Asian countries are increasingly consuming Western-type foods (e.g., incorporating drinks with meals) which collectively may also be contributing to obesity. Therefore, the aim of this study was to examine (a) associations between sugar-sweetened beverage (SSB) consumption as meal replacement and obesity and (b) associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A potential explanation for the association between shift work and obesity is the disruption in circadian rhythm, which results in an imbalance of glucose and lipid metabolism (Chew, Ang, et al, 2022; Wang et al, 2014). Additionally, individuals working the night shifts have been shown to have an increased preference for foods high in sugar and fat, potentially to stay awake (Chew, Gao, et al, 2022; Fradkin et al, 2019; Lin et al, 2019; Peplonska et al, 2019). Despite working in the healthcare sector and having knowledge regarding the importance of maintaining their metabolic health, nurses still face many barriers in adopting healthy behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation for the association between shift work and obesity is the disruption in circadian rhythm, which results in an imbalance of glucose and lipid metabolism (Chew, Ang, et al, 2022; Wang et al, 2014). Additionally, individuals working the night shifts have been shown to have an increased preference for foods high in sugar and fat, potentially to stay awake (Chew, Gao, et al, 2022; Fradkin et al, 2019; Lin et al, 2019; Peplonska et al, 2019). Despite working in the healthcare sector and having knowledge regarding the importance of maintaining their metabolic health, nurses still face many barriers in adopting healthy behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Associated with strenuous and stressful work conditions, like higher workloads (>12 hours/day) and shift work can be associated with worse sleep quality in general population [ 42 ]. In shift nurses, it was observed a higher intake of sweetened drinks and shorter period to have meals associated with worse sleep quality [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is impossible to know if the associations can be extrapolated to other populations, because of the labor conditions those population is exposed. It is known that shift workers can present a similar pattern of sleep and food intake [ 40 , 50 , 51 ], with a higher intake of energetic and sweetened drinks, even high-processed foods [ 41 , 43 , 52 ]. In this present research, it was not observed interactions between sweetened drinks and worse pattern of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies suggested that time and accessibility were other factors influencing shift workers' food choices and dietary intake (Bonnell et al, 2017 ). Workload has been linked to meal substitution using SSBs (Lin et al, 2019 ). Stress and time constraints in the workplace may increase workers' consumption of low‐nutrient foods (Leung et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%